2002
DOI: 10.1163/156855502760151634
|View full text |Cite
|
Sign up to set email alerts
|

Diacetylene-containing polymers XII. Synthesis and characterization of dye-containing poly(hexa-2,4-butadiynylenoxydibenzoates)

Abstract: Several novel diacetylene-containingpolymers containing diacetylenic groups in the main chains and dyes in the side-chains were synthesized using paraand meta-propargyloxybenzoicacids and four azo dyes. The polymers were synthesized by the oxidative coupling polymerization of dyecontaining bisacetylenic monomers, and were characterized and their thermal properties examined. All of the polymers gave thin lms with excellent optical quality by casting or spin coating. They showed T g at around 100 ± C and the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The four polymers used in this work, poly(hexa-2,4-diynylene-1,6-dioxydi benzoates) and poly(hexa-2,4-diynylene-1,6-dioxycinnamates), shown in the following structure, were prepared by the methods previously reported [6][7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four polymers used in this work, poly(hexa-2,4-diynylene-1,6-dioxydi benzoates) and poly(hexa-2,4-diynylene-1,6-dioxycinnamates), shown in the following structure, were prepared by the methods previously reported [6][7].…”
Section: Methodsmentioning
confidence: 99%
“…Recently however, the present authors have obtained series of novel polymers containing diacetylene groups in their main chains and polar chromophores as the side groups [5][6][7]. Their general structure is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…They were prepared by the methods described previously. 12 The polymers had inherent viscosities of 0.3-0.4 dl/g in N -methylpyrrolidone (NMP) at 25 • C. They were fractionated by precipitation technique from NMP/methanol, and low molecular weight portions soluble in chloroform were employed, so that they can be made into films by spin-coating from chloroform solution.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of the four polymers of which structures are shown in Scheme 1, were reported previously (7,8). Their films were prepared on an ITO coated glass substrate from their NMP solutions at 808C using a spin-coater equipped with heating gadget, and films with thickness of around 500 nm were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Present authors have reported previously series of novel polymers consisting of hexa-2,4-diynylene-1,6-dioxydibenzoates and dicinnamates in the main chains and Disperse Red 19 chromophore in the side chains (7,8), as shown in Scheme 1. The 2-NLO coefficients (d 33 ) of some of these polymers were high being over 250 pm/V (9, 10), and the d 33 depended most significantly on the main chain conformation, the para-polymers showing about 5 times greater d 33 than the corresponding meta-polymers.…”
mentioning
confidence: 99%